Analysis of The Relationship Between Information System Management, Demand Management, Revenue and Profit Management in Logistics Industries - Sultantio Hutabarat, Arnold; Umi Setyorini; Dede Rustaman; Teguh Prakoso; Eva Yuniarti Utami (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to investigate the application of the philosophy in the land cargo transportation sector. Researchers researched two companies in this sector: a courier service company and a truck-based goods transportation company. Semi-structured interviews were conducted with both companies to understand more about their operations, including reservation policies, prices, clients, etc. We also paid two visits to the company. We processed the data using the MS Excel Office program. The research results revealed that the studied company, the courier service company, adhered to a rigid pricing structure without taking the year into account, while the goods transportation company set prices based on distance without using historical data or demand per period. Additionally, we discovered errors in data recording at freight transportation companies, leading to the loss of crucial information. We propose performance indicators for both sectors, drawing from indicators used in other industries. Freight companies create segmentation based on months of the year, days of the week, and distance groups to enable better pricing strategies. However, analysis of the indicator calculation graph shows that the company does not sometimes charge a proportional price per kilometer traveled and does not segment by periods of the year. Thus, it is advisable to implement these practices to maximize company revenue.